Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1021/cm000249f
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Magnesium Hydroxide Sulfate Hydrate Whiskers

Abstract: Reaction of magnesium sulfate with aqueous ammonia in a hydrothermal condition (150−180 °C) produced a fibrous magnesium hydroxide sulfate hydrate (MHSH) with a composition corresponding to a stoichiometry of 4.34Mg(OH)2·MgSO4·xH2O. Chemical composition analysis showed that the quantity of x was more likely to be 2 rather than the well-known 3. The MHSH whiskers were about 0.3−2 μm in diameter and 40−100 μm in length, with an aspect ratio no less than 100. Selected area electron diffraction (SAED) and X-ray di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 9 publications
3
28
2
Order By: Relevance
“…It was reported that 513MOS whiskers with a diameter of 0.8−1.2 µm and a length of several to 200 µm were prepared at 130−170°C for 3−6 h, using MgSO 4 solution and Mg(OH) 2 or MgO solid [3,4]. 4.34 Mg(OH) 2 ·MgSO 4 ·xH 2 O whiskers with a diameter of 0.3−2.0 µm and a length of 40−100 µm were synthesized at 150−180℃ for 16 h, using MgSO 4 and ammonia as the reactants [5]. 513MOS nano-ribbons with a length up to several micrometers, a width of 60−300 nm and a thickness of 16−50 nm were formed after mixing MgSO 4 and NaOH−ethanol solution at room temperature followed by treating the precursor at 100°C for 24 h [6].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that 513MOS whiskers with a diameter of 0.8−1.2 µm and a length of several to 200 µm were prepared at 130−170°C for 3−6 h, using MgSO 4 solution and Mg(OH) 2 or MgO solid [3,4]. 4.34 Mg(OH) 2 ·MgSO 4 ·xH 2 O whiskers with a diameter of 0.3−2.0 µm and a length of 40−100 µm were synthesized at 150−180℃ for 16 h, using MgSO 4 and ammonia as the reactants [5]. 513MOS nano-ribbons with a length up to several micrometers, a width of 60−300 nm and a thickness of 16−50 nm were formed after mixing MgSO 4 and NaOH−ethanol solution at room temperature followed by treating the precursor at 100°C for 24 h [6].…”
Section: Introductionmentioning
confidence: 99%
“…The TGA curve displays an apparent two-step process in the temperature range from 25 to 700 8C, with two sharp, accompanying DTG peaks at 301 and 411 8C in the first and second stage, respectively. It is believed that the degradation processes are described by the following reactions: [8] The endothermic decomposition, the accompanying release of water vapor and the generation of inorganic components on the MHSH whisker residue at the temperature that the polymers themselves degrade, correspond with the FR mechanism, that is based on the physical effects governing the endothermic processes.…”
Section: Resultsmentioning
confidence: 99%
“…[7] Recently, magnesium hydroxide sulfate hydrate (MHSH) whiskers were systematically investigated by Ding and Ma. [8,9] It was found that the MHSH whiskers degraded endothermically, accompanied by the release of water vapor, and leaving fiber-shaped degradation products. This process indicates that the MHSH whisker has the fundamental requirements of a flame retardant (FR) additive, according to the flame retardant mechanism based on physical effects governing the endothermic processes, such as magnesium hydroxide (MH) suggested by Hornsby and Watson.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2]. MHSH whiskers are important inorganic materials [3,4], with various distinctive properties including low toxicity, high corrosion resistance, low density, high thermal stability and high elastic modulus [5][6][7][8][9], which have been widely used as resin additives of flame retardant for polymers, fillers, reinforcing agent, and acidic waste neutralizer for environmental protection, etc. [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…MHSH whiskers are usually prepared via hydrothermal synthesis [1,14,15]. By using MgSO 4 and NH 3 ·H 2 O as the starting materials, MHSH whiskers with an aspect ratio larger than 100 were synthesized at 150 • C for 16 h [5]. Moreover, a variety of magnesium sources such as magnesium hydroxide, magnesium oxide, magnesium sulfate [16,17], as well as raw serpentine and magnesite ores or even serpentine mine tailings [18], were also used as the starting materials.…”
Section: Introductionmentioning
confidence: 99%